L^p REGULARITY OF THE SZEGÖ PROJECTION ON THE SYMMETRISED POLYDISC. Issue 3 (12th December 2022) - HAN, KAIKAI; TANG, YANYAN
Abstract: We consider the L^p -regularity of the Szegö projection on the symmetrised polydisc G_n . In the setting of the Hardy space corresponding to the distinguished boundary of the symmetrised polydisc, it is shown that this operator is L^p -bounded for p(2-1/n, 2+1/(n-1)) .